Conceptualising innovative lighting interventions for suicide, trespass and risky behaviour on the railway. (January 2023) - Hallewell, MJ; Ryan, B; Hughes, N; Coad, N
Three behaviour types – suicide, trespass and risky behaviours, which can result in entry to railway tracks – present an ongoing challenge to the rail industry for fatality prevention. Many preventative interventions exist, operating at different stages in the timeline of a person's decision to access the tracks to the point that they have entered and remain in the track area. However, there is little understanding of the impacts of interventions on the behaviours in question. This paper outlines the generation of the functional requirements for the use of lighting as safety interventions, which can contribute towards the development and evaluation of such interventions. The study includes the analysis of literature on how lighting has been used to date in the prevention of suicide, trespass and other risky behaviour on railway property. Interviews were carried out with 13 key stakeholders who have expertise in the behaviours in question and awareness of the range of safety interventions used in practice in railway settings. The analysis explores how lighting can be used to influence these different behaviour types. Functionalities that are both theoretically and empirically promising are identified. These functionalities include the need for reactive environmental changes, novelty, ability to influence decision-making and ability to support a human response, for example, through highlighting to staff when someone has entered the tracks. These functionalities offer developers a framework for developing (and subsequently evaluating) a range of novel intervention technologies, which could highlight specific lighting properties that could influence behaviour.